2020
DOI: 10.1007/s10530-020-02251-3
|View full text |Cite
|
Sign up to set email alerts
|

Endemic species predation by the introduced smooth-billed ani in Galápagos

Abstract: The introduced smooth-billed ani Crotophaga ani has become widespread across the Galápagos archipelago in the past half-century. It is known to predate upon a range of native and endemic species, and is a potential vector for the spread of invasive plants and parasites. Here we report previously undocumented examples of smooth-billed ani predation in Galápagos, including that of an endemic racer snake and a scorpion. We highlight the possibility of smooth-billed anis having a serious impact on the endemic Galá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Contrary to other countries in the region -whether mega-diverse or not (Heringer et al 2021;Adelino et al 2021;Duboscq-Carra et al 2021), Ecuadorian institutional authorities, at least in the Galapagos Islands, have invested actively in invasive species management actions. One of the reasons is the body of research about the massive impact that invasive species have on the Galapagos resident biota (Jäger et al 2009;Jäger et al 2013;Rivas-Torres and Rivas 2018;Cooke et al 2020), triggering investment to control or eradicate these species. However, ecological damage is more difficult to monetize and consequently, fewer costs are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to other countries in the region -whether mega-diverse or not (Heringer et al 2021;Adelino et al 2021;Duboscq-Carra et al 2021), Ecuadorian institutional authorities, at least in the Galapagos Islands, have invested actively in invasive species management actions. One of the reasons is the body of research about the massive impact that invasive species have on the Galapagos resident biota (Jäger et al 2009;Jäger et al 2013;Rivas-Torres and Rivas 2018;Cooke et al 2020), triggering investment to control or eradicate these species. However, ecological damage is more difficult to monetize and consequently, fewer costs are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ani were introduced to the Galápagos during the 1960s to remove ticks from introduced cattle on Santa Cruz, spread to other islands during the 1990s, and the population of ca. 250,000 now consumes Darwin's Finch chicks, endemic Galápagos cricket (large painted locust, Gryllus abditus), Galápagos carpenter bee (Xylocopa darwini), Galápagos racer snake, Galápagos lava lizard (Microlophus albemarlensis) and a range of other endemic fauna [70][71][72]. They also consume and distribute the seeds of introduced blackberry and guava, and other species, thereby contributing to significant shifts in local ecosystem function [71,73,74].…”
Section: Discussionmentioning
confidence: 99%
“…250,000 now consumes Darwin's Finch chicks, endemic Galápagos cricket (large painted locust, Gryllus abditus), Galápagos carpenter bee (Xylocopa darwini), Galápagos racer snake, Galápagos lava lizard (Microlophus albemarlensis) and a range of other endemic fauna [70][71][72]. They also consume and distribute the seeds of introduced blackberry and guava, and other species, thereby contributing to significant shifts in local ecosystem function [71,73,74]. The finding that avian predation was the second leading cause of offspring mortality in Medium Tree Finch points to owl and/or ani, the only two avian predators on the island.…”
Section: Discussionmentioning
confidence: 99%
“…T. b. galapagoensis larvae presumably preyed on other animals prior to the arrival of S. quinquefasciatus to the island, but our finding also suggests that the beetle larvae have not developed a tadpole specialisation-decreasing its potential as a natural control agent. A recent study showed that an introduced bird, the smooth-billed ani (Crotophaga ani), feeds on S. quinquefasciatus adults in Galápagos, but predation rates are also too low to have an effect on the frog's population size (Cooke et al 2020).…”
Section: Discussionmentioning
confidence: 99%